OddEasy : design and development of a game for learning probability - Joshua Aristo Nathaniel Hendra (2017)
Probability is the study of random phenomena. It contains many real life applications, a strong understanding of which can greatly improve one’s decision making ability when faced with choices involving uncertainity. However, many find probability theory to be an unintuitive study, struggling when faced with problems of increasing complexity such as conjuctions of various events and conditional probability. This project aims to develop OddEasy, a puzzle game which also serves as interactive tool for visualizing probability. The game is a desktop and web-based application, which allows users to experiment with various combinations of probability-related events and rules, as well as observe the visualized outcome of said probabilistic setting. While the game can be used by anyone to serve as a calculator or visualizer of probability, it is mainly aimed to be an assistive tool in teaching the basics of probability to students. Designed to promote interactive and visual learning, it is hoped that through playing the game and solving the included probability questions, students can build a stronger foundation for probability from a young age. The game is developed with a focus on user experience, simplicity and approachable UI design. However, the system is also designed to be powerful, able to be used to visualize as many different scenarios as possible. Additionally, while it is developed to be a complete, release-ready application, it was also developed with maintainability and flexibility in mind to support future improvements.